2022
DOI: 10.18632/aging.204069
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with chloroquine increases lifespan in middle-aged male mice possibly via autophagy modulation, proteasome inhibition and glycogen metabolism

Abstract: Previous studies have shown that the polyamine spermidine increased the maximum life span in C. elegans and the median life span in mice. Since spermidine increases autophagy, we asked if treatment with chloroquine, an inhibitor of autophagy, would shorten the lifespan of mice. Recently, chloroquine has intensively been discussed as a treatment option for COVID-19 patients. To rule out unfavorable long-term effects on longevity, we examined the effect of chronic treatment with chloroquin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Related to the work of Li et al, Doeppner et al (2022) also reported a chloroquine-mediated increase in the lifespan of rodents, in this case mice 17 .…”
Section: Geroprotective Activities Of Chloroquinementioning
confidence: 81%
See 1 more Smart Citation
“…Related to the work of Li et al, Doeppner et al (2022) also reported a chloroquine-mediated increase in the lifespan of rodents, in this case mice 17 .…”
Section: Geroprotective Activities Of Chloroquinementioning
confidence: 81%
“…LC3-II is generated by the conjugation of cytosolic LC3-I to phosphatidylethanolamine on the surface of nascent autophagosomes. Doeppner et al showed that the CQ-treated mice exhibited a dose-dependent increase in LC3B-II as well as p62 in the liver and heart, as con rmed by transmission electron microscopy 17 .…”
Section: Mechanism Studiesmentioning
confidence: 88%
“…The role of CQ as an autophagy inhibitor has garnered recent attention, with investigations focusing on its potential opposing effect to spermidine on lifespan in model organisms (Doeppner et al., 2022). Against all odds, male NMRI mice treated with chloroquine at a dose of 50 mg/kg/day, starting at 500 days old and continuing for 286 days, significantly outlived the control group, with an average lifespan of 786 days compared to 689 days in the controls.…”
Section: Resultsmentioning
confidence: 99%
“…Various treatments including rapamycin, resveratrol, spermidine, and others have been proposed as potential lifespan‐extending treatments (Doeppner et al., 2022). However, despite the promising results obtained in organism models such as yeast, worms, and flies, the translatability of these interventions across species of increasing complexity and to humans is still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…The increment in ubiquitin and 20s proteasome subunit in denervated muscles of CQ-treated rats was reported (Kimura et al, 2009). In addition, CQ treatment (50 mg/kg during 250) expanded the median and maximum lifespan of male mice, this effect was related to an increment in the autophagosome-like structures containing cytoplasmic organelles with changes in the proteasome activity (Doeppner et al, 2022). The discrete data of oxidation protein in the co-exposure CQ-metal(loid) could be mediated by autophagic-lysosome-and ubiquitin-proteasome-proteolysis pathways, that need further studies.…”
Section: Discussionmentioning
confidence: 95%